Irregular practices in drugstores in the offer of products for children under three years old - Roberta Almeida Silva Soares; Elisa Natany Silva Pinheiro; Maria Hortência Teixeira Diniz; Ana Paula Bortoletto Martins; Antônio Marcos Machado de Oliveira; Leandro Alves Pereira; Luciana Saraiva da Silva; Ana Elisa Madalena Rinaldi (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To analyze the compliance with the commercialization of children's products included in the Brazilian Code of Marketing of Infant and Toddlers Food and Childcare-Related Products (NBCAL) in drugstores in Uberlândia/MG. Methods: A cross-sectional study was carried out in 143 drugstores that sold infant products: infant formula (IF), follow-up IF, nipples, teats, pacifiers and nipple shields; FI for young children, transition foods and cereal-based foods, fluid or powdered milk, modified/similar milks of plant origin and dairy compounds. The location of drugstores in the five geographic sectors was performed by geoprocessing. The data collected were: types of promotion and types of drugstore administration (drugstore chains/drugstores with independent administration). Irregular commercial promotion was expressed as absolute and relative frequencies. Results: Irregular commercial promotion was found in 11.7% of nipples, pacifiers and bottles, in 10.0% of IF and follow-up formula, in 9.5% of IF for young children, in 11.1% fluid or powdered milk, in 25.0% of transition foods and cereal-based foods and in 59.1% of dairy compounds. In commercial drugstore chains, the presence of promotion for dairy (81.8 vs. 28.6%, respectively) was higher than in drugstores with independent administration. The opposite ocurred for fluid or powdered milk, modified and similar milks of plant origin. The downtown and eastern sectors had the highest percentages of promotions (26%). Conclusions: NBCAL violations still occur in drugstores, mainly in the sale of young children's foods and in the commercial network drugstores.